The planets (Bantam Books, 1985)
Contents: The Planets is an extraordinary new part of that adventure. It is the first joint effort of America's finest space scientists, the world's most popular science fiction authors, and the most influential space artists, who take us on a tour of the solar system as it exists now and as it may exist once the planets are fully explored